Godly reformers and their opponents in early modern England : religion in Norwich, c.1560-1643 - Reynolds, Matthew, 1973- (Studies in modern British religious history, 2005)
"Close examination of the divided religious life of Norwich in the late sixteenth and early seventeenth centuries, with wider implications for the country as a whole"--Provided by publisher